Proceedings of the Tenth International Conference on Motion in Games 2017
DOI: 10.1145/3136457.3136466
|View full text |Cite
|
Sign up to set email alerts
|

Normalized Euclidean distance matrices for human motion retargeting

Abstract: Figure 1: (a) Example pose where the actor's hands come to a close distance. The same pose retargeted on a skeleton with longer forearms by (b) simply transferring joint angles or (c) using our normalized Euclidean distance matrix approach. ABSTRACTIn character animation, it is often the case that motions created or captured on a specific morphology need to be reused on characters having a different morphology while maintaining specific relationships such as body contacts or spatial relationships between body … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…By representing this animation by distances, we can construct the graph G with the edge set E * as in equ. (1), where our depth parameter τ is set to 3. Moreover, we added the following set of edges:…”
Section: A Non-monotone Spectral Gradient Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…By representing this animation by distances, we can construct the graph G with the edge set E * as in equ. (1), where our depth parameter τ is set to 3. Moreover, we added the following set of edges:…”
Section: A Non-monotone Spectral Gradient Methodsmentioning
confidence: 99%
“…This is a very delicate step, because the inclusion of large changes in the modified distances may cause large distance incompatibilities, and spoil the simulations. One possible technique for modifying the distances related to pairs {u, v} ∈ E S in accordance with new skeletal structure was recently presented in [1,23]. Some preliminary results can be viewed in a video clip associated to the paper [1] (downloadable from the conference website).…”
Section: Non-rigid Skeletal Structuresmentioning
confidence: 99%
“…3, representing the animation of character A, to character B (in other words, it is imposed that ≡ ). However, the Euler angles in are not able to take into consideration the spatial relationship between pairs of character joints [2,10], and as a consequence undesired effects may be introduced in the animation. Typical undesired effects include creating body contacts that were not present in the original animation, or to miss body contacts that actually occur in the original animation.…”
Section: Human Motion Adaptationmentioning
confidence: 99%
“…It is important to point out the two different roles of and in equ. (2). The former is one of the weights associated to the edges of the graph , which corresponds to the available distance value between a vertex pair.…”
Section: Introductionmentioning
confidence: 99%
“…This article focuses on a particular application of the dynDGP, where the main interest is in analyzing human motions through the study of animated skeletal structures which resemble the human body [20]. Some initial works have shown that tools for distance geometry can be employed in this context [2,17], but they consider, as in the majority of the applications in distance geometry, the Euclidean distance as a metric.…”
Section: Introductionmentioning
confidence: 99%